Mechanisms of gut microbiota-immune-host interaction on glucose regulation in type 2 diabetes - Zhou, Yu-Dian; Liang, Feng-Xia; Tian, Hao-Ran; Luo, Dan; Wang, Ya-Yuan; Yang, Shu-Rui (Frontiers in Microbiology, 2023)
Intestinal absorption of food is one of the sources of glucose. Insulin resistance and impaired glucose tolerance caused by lifestyle and diet are the precursors of type 2 diabetes. Patients with type 2 diabetes have trouble controlling their blood sugar levels. For long-term health, strict glycemic management is necessary. Although it is thought to be well correlated with metabolic diseases like obesity, insulin resistance, and diabetes, its molecular mechanism is still not completely understood. Disturbed microbiota triggers the gut immune response to reshape the gut homeostasis. This interaction not only maintains the dynamic changes of intestinal flora, but also preserves the integrity of the intestinal barrier. Meanwhile, the microbiota establishes a systemic multiorgan dialogue on the gut-brain and gut-liver axes, intestinal absorption of a high-fat diet affects the host's feeding preference and systemic metabolism. Intervention in the gut microbiota can combat the decreased glucose tolerance and insulin sensitivity linked to metabolic diseases both centrally and peripherally. Moreover, the pharmacokinetics of oral hypoglycemic medications are also influenced by gut microbiota. The accumulation of drugs in the gut microbiota not only affects the drug efficacy, but also changes the composition and function of them, thus may help to explain individual therapeutic variances in pharmacological efficacy. Regulating gut microbiota through healthy dietary patterns or supplementing pro/prebiotics can provide guidance for lifestyle interventions in people with poor glycemic control. Traditional Chinese medicine can also be used as complementary medicine to effectively regulate intestinal homeostasis. Intestinal microbiota is becoming a new target against metabolic diseases, so more evidence is needed to elucidate the intricate microbiota-immune-host relationship, and explore the therapeutic potential of targeting intestinal microbiota.